Risk Prediction of Rock Bursts and Large Deformations in YL Tunnel of the Chongqing–Kunming High-Speed Railway - Liu, Yuxuan; Zhang, Yuqi; Su, Peidong; Zhang, Guangze; Qiu, Peng; Tang, Lin (Frontiers in Earth Science, 2022)
The YL Tunnel of the Chongqing–Kunming high-speed railway project, a key project of the whole line, is a typical ultra-long deep tunnel facing geologic problems, such as rock bursts, large deformation, water inrush, and toxic or harmful gas leakage, among which high ground stress results in the most serious damage. This study incorporates existing studies and materials, as well as data on ground stress obtained through tests using the hydrofracturing technique. The areas with rock bursts and large deformations were divided accordingly, and preventive measures were expounded. The results showed that the areas predicted as high risk of severe rock burst were D1K338 + 945–D1K339 + 025 and D1K339 + 075–D1K339 + 220, which is of significance when constructing the whole Chongqing–Kunming high-speed railway and may even be instructive in railway construction in the southwest region of China.